Are some deaths worse than others? Result from a discrete choice experiment - Angela Robinson; Judith Covey; Anne Spencer; Graham Loomes (Queen Mary University of London, Department of Economics, 2007)
Previous research has shown that people wish a premium to be placed on the prevention of certain types of deaths as they perceive those deaths as 'worse' than others. The research reported in this paper is an attempt to quantify such a 'bad death' premium via a discrete choice experiment (DCE). The four underlying attributes included were: the age of the victim, who was most to blame for the death, the severity of the victim's pain and suffering in the period leading up to death, and the duration of the victim's pain and suffering in the period leading up to death. In addition, a fifth attribute - number of deaths - was included in order to provide a quantitative scale against which to measure the bad death premium. The results show that each of the 4 underlying attributes did matter to respondents in determining whether deaths were worse than others, but also uncovered marked insensitivity to variations in the number of those deaths. The implication of our findings for the use of quantitative variables in DCEs is discussed.
Keywords: H5; I10; 330; Discrete choice experiment; Value of preventing a fatality; Relative weights; Insensitivity; Sterblichkeit; Angst; Diskrete Entscheidung; Test; Sch\~AƒÂtzung; Gro\~AƒÅbritannien